Perkembangan Tradisi Senandung di Kabupaten Asahan - Soiman Soiman; Khairul Arif; Nurhayati Marpaung (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2021)
Culture is a habit that is present in society and has benefits for maintaining and developing a way of life. There are so many traditional cultures that exist in Asahan Regency, researchers decided to choose the